Swaddle bath vs. tub bath for physiological outcomes and skin microbiota in late preterm infants: a randomized controlled trial - Jia, Xiaoqin; Wu, Yihong; Huang, Zhaomei; Fan, Wanying; Chen, Jun; Huang, Xiudan; Feng, Huihua (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the effects of two bathing methods, swaddle bath and tub bath, on physiological parameters and skin microbiota in late preterm infants.DesignProspective, no-blinded, randomised controlled trial.SettingNeonatal Intensive Care Unit in Foshan.Methods56 late preterm infants were randomly divided into two groups: Intervention Group (swaddle bath, n = 28), control group (tub bath, n = 28). Physiological parameters, hemodynamics, stress responses and skin colony counts were evaluated pre(T0), immediate(T1), 30 min after bathing(T2).ResultsThe mean changes of rectal temperature, heart rate, respiration, and perfusion index (PI) in the intervention group were significantly higher than that of the control group immediately after bathing. The swaddle bath group showed less stress during the bathing process compared to the tub bath group (Crying: 1 vs. 8, p = 0.03, Clenched hands: 4 vs. 11, p = 0.04). No difference was found between the two groups, in terms of different peripheral oxygen saturation (SpO2), pulse variability index (PVI), or the number of skin colonies.ConclusionSwaddle bath is a more recommended bathing for late preterm infants, as it ensures stable vital signs and blood perfusion while reducing stress manifestations during the bathing process.Clinical Trial Registrationhttps://www.chictr.org.cn/indexEN.html, identifier ChiCTR2400087426.